Fuzzy Logic Controller for Cascaded H-Bridge Multilevel Inverter - N. Sivakumar; A. Sumathi (Institute of Advanced Engineering and Science, 2015)
This paper proposes fuzzy logic controller based seven-level hybrid inverter for photovoltaic systems with sinusoidal pulse width-modulation (SPWM) techniques. Multi-Level Inverter technology have been developed in the area of high-power medium-voltage energy scheme, because of their advantages such as devices of high dv/dt rating, higher switching frequency, unlimited power processing, shape of output waveform and desired level of output voltage, current and frequency adjustment.This topology can be used there by enabling the scheme to reduce the Total Harmonic Distortion (THD) for high voltage applications. The Maximum Power Point Tracking algorithm is also used for extracting maximum power from the PV array connected to each DC link voltage level. The Maximum Power Point Tracking algorithm is solved by Perturb and Observer method.It has high performance with low Total Harmonic Distortion and reduced by this control strategy. The proposed system has verified and THD is obtained by using MATLAB/simulink.The result is compared with the hardware prototype working model.